53 Fast not always better – diabetic screening at time of stemi. (5th October 2017) - O'Hare, D; Mostafa, K; Mustafa, M; Gorecka, M; Hennessey, B; MacNeill, B; Crowley, J
Abstract : Introduction: The European Society of Cardiology recommends that all patients with coronary artery disease should have their glycaemic state evaluated to enable risk stratification and optimal management. The World Health Organisation and American Diabetes Association agree on diagnostic criteria, and allow the use of Fasting Plasma Glucose, Two-hour plasma glucose challenge or HbA1 c to establish a diagnosis of Diabetes [1] . The purpose of this study was to assess how random and fasting plasma glucose tests compare to HbA1 c as a diagnostic tool during the acute phase of an ST elevation MI. Methods: We reviewed all patients admitted to a tertiary referral centre with HIPE coded diagnosis of ST elevation myocardial infarction from 1st January to December 31st 2016. Their blood glucose and HbA1 c results during their inpatient stay were analysed and the Pearson correlation coefficient of fasting glucose and HbA1 c was calculated to assess their relationship. Results: Of 164 patients included for analysis, 135 had their glycaemic state evaluated (82%), a further 20 patients (12%) were repatriated to a local hospital prior to glycaemic testing. The most common test was fasting plasma glucose (49%), followed by Hba1 C (39%) and random glucose (38%). 37 of the 64 HbA1 c tests (58%) returned a normal result (≤38 mmol/mol). Within the cohort of patients with a normal HbA1 c, 41% had an abnormal fasting or random plasma levels. 4/15 (27%) of the pre-diabetic HbA1 c results were preceded by normal fasting or random glucose levels. The Pearson correlation coefficient between Fasting plasma glucose and HbA1 c was 0.66, indicating a moderate correlation. 19/164 patients (12%) had a pre-existing diagnosis of diabetes mellitus. A new diagnosis of Diabetes Mellitus was confirmed by HBa1 c testing (≥48 mmol/mol) in 4 patients (2.8%), and a pre-diabetic state (39 to 47 mmol/mol) was diagnosed in 14 patients (9.7%) without a previous diagnosis. Conclusions: There is a significant under diagnosis of Diabetes Mellitus in patients presenting with STEMI. Routine glycaemic testing can identify previously undiagnosed patients. Our study shows a moderate correlation between fasting plasma glucose and HbA1 c. Plasma glucose levels are severely affected during the acute inflammatory response associated with STEMI, 1 and therefore HbA1 c represents an alternative for accurate assessment of glycaemic state. Routine use of HbA1 c testing on patients with STEMI will help diagnose new diabetics, assess glycaemic control in patients with a pre-existing diagnosis, and identify those patients who are in a pre-diabetic state. 2